2006
DOI: 10.1002/rcm.2827
|View full text |Cite
|
Sign up to set email alerts
|

2B or not 2B, that is the question: further investigations into the use of pencil as a matrix for matrix‐assisted laser desorption/ionisation

Abstract: The effective use of pencil as a matrix for matrix-assisted laser desorption/ionisation (MALDI) for the study of actinides has previously been demonstrated (Black et al., Rapid Commun. Mass Spectrom. 2006; 20: 1053). Here, the scope of the types of molecules amenable to analysis by this method has been extended, establishing that $90% of a library containing 50 diverse small molecules can be successfully analysed by this technique. Further, the role played by the bulk materials present in the different pencil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 17 publications
1
47
0
Order By: Relevance
“…To date a number of ionization techniques that belong to SALDI have been proposed,1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, ...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date a number of ionization techniques that belong to SALDI have been proposed,1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, ...…”
Section: Introductionmentioning
confidence: 99%
“…nanoparticles as typical, in treatable forms such as suspension liquids in order to ensure that the photon energies of the laser can act to desorp and ionize analytes 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45. Indeed, the soft ionization laser method such as the original form of MALDI also belongs to this category 1.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, samples can be stored on TLC plates for further analyses, which is not possible in other chromatography techniques. 17 Although the use of pencil lead as a MALDI matrix has been reported, 26,27 it is far from common. To our knowledge, only one article describes the use of pencil lead as a TLC-MALDI matrix, where a pencil line was pre-drawn on the TLC plate for the analysis of porphines.…”
Section: Resultsmentioning
confidence: 99%
“…17 Because powdered graphite is not easy to handle, pencil lead has recently been used as a new matrix material. 26,27 Pencil lead has also been used in the TLC separation and MALDI analysis of porphines, where a line was pre-drawn with a pencil on the TLC plate where the sample was separated, followed by laser irradiation on the pencil line to obtain mass spectra. 28 The current study describes, to our knowledge, the first reported detection of esters using TLC-MALDI-MS with a pencil lead matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were extensively diluted with 50:50 methanol/water solution to desired concentrations prior to analysis. Taking the analysis of glucose as an example, we defined a positive detection of nitrate-attached glucose ions based on the peak detection criteria of above a signal-to-noise (S/N) to 3 ( Figure 3) [29,[37][38][39]. Experimentally determined limit of detections (LODs) for the above mentioned analytes were listed in the Supplementary Table 1.…”
Section: Nedn As a Negative Ion-mode Matrix For Small Molecule Analysismentioning
confidence: 99%